Atrial Fibrillation Screen, Management And Guideline Recommended Therapy (AF SMART II) in the rural primary care setting: an implementation study protocol. Issue 10 (31st October 2018) - Orchard, Jessica J; Neubeck, Lis; Freedman, Ben; Webster, Ruth; Patel, Anushka; Gallagher, Robyn; Li, Jialin; Hespe, Charlotte Mary; Ferguson, Caleb; Zwar, Nicholas; Lowres, Nicole
Abstract : Introduction: Screening for atrial fibrillation (AF) in people ≥65 years is now recommended by guidelines and expert consensus. While AF is often asymptomatic, it is the most common heart arrhythmia and is associated with increased risk of stroke. Early identification and treatment with oral anticoagulants can substantially reduce stroke risk. The general practice setting is ideal for opportunistic screening and provides a natural pathway for treatment for those identified. This study aims to investigate the feasibility of implementing screening for AF in rural general practice using novel electronic tools. It will assess whether screening will fit within an existing workflow to quickly and accurately identify AF, and will potentially inform a generalisable, scalable approach. Methods and analysis: Screening with a smartphone ECG will be conducted by general practitioners and practice nurses in rural general practices in New South Wales, Australia for 3–4 months during 2018–2019. Up to 10 practices will be recruited, and we aim to screen 2000 patients aged ≥65 years. Practices will be given an electronic screening prompt and electronic decision support to guide evidence-based treatment for those with AF. De-identified data will be collected using a clinical audit tool and qualitative interviews will be conducted with selected practice staff. A process evaluation and cost-effectiveness analysis will also be undertaken. Outcomes include implementation success (proportion of eligible patients screened, fidelity to protocol), proportion of people screened identified with new AF and rates of treatment with anticoagulants and antiplatelets at baseline and completion. Results will be compared against an earlier metropolitan study and a 'control' dataset of practices. Ethics and dissemination: Ethics approval was received from the University of Sydney Human Research Ethics Committee on 27 February 2018 (Project no.: 2017/1017). Results will be disseminated through various forums, including peer-reviewed publication and conference presentations. Trial registration number: ACTRN12618000004268; Pre-results.